Degradation of Organic Dye Congo Red by Heterogeneous Solar Photocatalysis with Bi2S3, Bi2S3/TiO2, and Bi2S3/ZnO Thin Films - Carrillo, Amanda (2024)
In this work, bismuth sulfide (Bi2S3) thin films were deposited by a chemical bath deposition (CBD) technique (called soft chemistry), while titanium dioxide (TiO2) nanoparticles were synthesized by sol–gel and zinc oxide (ZnO) nanoparticles were extracted from alkaline batteries. The resulting nanoparticles were then deposited on the Bi2S3 thin films by spin coating at 1000 rpm for 60 s each layer to create heterojunctions of Bi2S3/ZnO and Bi2S3/TiO2. These materials were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDX). The optical and contact angle analyses were undertaken by UV–Vis spectroscopy and a contact microscopy angle meter, respectively. The calculated band gap values were found to be between 1.9 eV and 2.45 eV. The Bi2S3 presented an orthorhombic structure, the TiO2 nanoparticles presented an anatase structure, and the ZnO nanoparticles presented a wurtzite hexagonal crystal structure. Furthermore, heterogeneous solar photocatalysis was performed using the Bi2S3, Bi2S3/ZnO, and Bi2S3/TiO2 thin film combinations, which resulted in the degradation of Congo red increasing from 8.89% to 30.80% after a 30 min exposure to sunlight.